On the Design of Maze Wanderer Robot - Abdulhamid, Mohamad (Universitas Airlangga, 2023)
This paper focuses on designing, programming and implementing a maze wonderer robot that takes the commands todictate its direction of motion based on the obstacle avoidance. A program is to be written to give the robot its intelligence. Thepaper will as well be restricted to a motorized car which will be given the intelligence to be able to navigate through a given maze.